KOMPOSISI, STRUKTUR DAN DENSITAS PADUAN U-7Mo-xSi - Supardjo; Kadarjono, Agoeng; Setiawan, Jan; Suryaman, Ganisa Kurniati (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
The structure of U-7Mo-xSi (x = 1, 2, and 3%) alloy was studied to obtain a new uranium alloy suitable for use as a candidate for high-density uranium research reactor fuel. The U-7Mo-xSi alloy was made by melting technique using an arc furnace. The characterization of the alloy includes chemical composition, density, and structural phases to identify the phases contained in the alloy. The hardness test was also done. The density characterization results show that U content and density of the alloy decrease with increasing of Si content in the U-7Mo-xSi alloy. On the other hand, the hardness of the alloy increases with increasing of Si content. The X-ray diffraction pattern of U-7Mo-xSi alloy was observed from diffraction angle of 25° to 95°. The results indicate the presence of U-γ, U3Si2, and U3Si2Mo phases. The higher the Si content, the more U3Si2 phase is formed and the more the hardness increases due to the formation of bonds between Si and Si.